Does government spending crowd in private consumption? Theory and empirical evidence for the euro area - Günter Coenen; Roland Straub (European Central Bank (ECB), 2005)
In this paper, we revisit the effects of government spending shocks on private consumption within an estimated New-Keynesian DSGE model of the euro area featuring non-Ricardian households. Employing Bayesian inference methods, we show that the presence of non-Ricardian households is in general conducive to raising the level of consumption in response to government spending shocks when compared with the benchmark specification without non-Ricardian households. However, we find that there is only a fairly small chance that government spending shocks crowd in consumption, mainly because the estimated share of non-Ricardian households is relatively low, but also due to the large negative wealth effect induced by the highly persistent nature of government spending shocks.
Keywords: E32; E62; 330; DSGE modelling; euro area; Fiscal Policy; non-Ricardian households; Öffentliche Ausgaben; Privater Konsum; Geldpolitik; Eurozone; Schock; Stochastischer Prozess; Dynamische Wirtschaftstheorie; Allgemeines Gleichgewicht; Theorie; EU-Staaten